Unloading‐Based Stiffness Characterisation of Cement Pastes During the Second, Third and Fourth Day After Production. (April 2015) - Karte, P.; Hlobil, M.; Reihsner, R.; Dörner, W.; Lahayne, O.; Eberhardsteiner, J.; Pichler, B.
Abstract: The stiffness evolution of binder 'cement paste' is triggering the stiffness of concrete. In the engineering practice, concrete formworks are typically removed 24 h after production. This underlines that knowledge on mechanical properties of cementitious materials during the second, third and fourth day after production is of high relevance for the ongoing construction process. This provides the motivation to perform early‐age stiffness characterisation on hydrating cement pastes, by means of the following three test methods. Unloading modulus is determined using a novel setup for non‐destructive uniaxial compression testing including overdetermined deformation measurements. Dynamic Young's moduli are obtained from ultrasonics experiments. Isothermal differential calorimetry allows for linking the observed temporal evolution of early‐age stiffness to the hydration degree of cement. Pastes with three different compositions are investigated, defined in terms of the initial water‐to‐cement mass ratio w / c and the initial water‐to‐solid (binder) mass ratio w / s . Pure cement pastes exhibit  w / c  =  w / s  = 0.50 and w / c  =  w / s  = 0.42, respectively. A fly ash‐blended cement paste refers to a cement mass replacement level of 16%, and this is related to w / c  = 0.50 and w / s  = 0.42. Both unloading moduli and dynamic Young's moduli of all three materials increase practically linearly with increasing hydration degree, in the investigated regime of hydration degrees ranging from 40 to 60%. Fly ash does not contribute significantly to the early‐age hydration of the material, i.e. it represents a quasi‐inert part of the material's microstructure, exhibiting a significant stiffening effect.